Applied surgical physiology vivas - Kanani, Mazyar (Greenwich Medical Media Ltd., 2004)
An understanding of basic sciences is the cornerstone of medical and surgical training, and viva examinations in particular remain a source of anxiety for many candidates. Applied Surgery Physiology Vivas follows the same format as the hugely popular General Pathology Vivas and Surgical Critical Care Vivas. It gives candidates a means of practising some of the most common questions that they will be asked in their viva examinations, with detailed model answers and diagrams to highlight key points where necessary.